1970
DOI: 10.3329/bjpt.v18i2.9306
|View full text |Cite
|
Sign up to set email alerts
|

<i>Cinnamomum alexei</i> Kosterm. (Lauraceae) - A new record for India

Abstract: Keywords: Cinnamomum alexei; New record; India.DOI: http://dx.doi.org/10.3329/bjpt.v18i2.9306Bangladesh J. Plant Taxon. 18(2): 199-201, 2011 (December)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…1969, -Type: Buwalda 3618 (holo BO; iso L), Java, Tjampaka near Tjidadap, Mt Karang; Kumar et al [2] Cinnamomum alexei is a beautiful tree worth introducing as an avenue plant. Its flowers seldom open widely.…”
Section: Short Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…1969, -Type: Buwalda 3618 (holo BO; iso L), Java, Tjampaka near Tjidadap, Mt Karang; Kumar et al [2] Cinnamomum alexei is a beautiful tree worth introducing as an avenue plant. Its flowers seldom open widely.…”
Section: Short Communicationmentioning
confidence: 99%
“…Santhosh et al [2] reported this species for India from the Ponmudi hills of Thiruvananthapuram district in Kerala. This is the one and only locality for this rare plant in India.…”
mentioning
confidence: 97%
“…amphor tree, (Karpura) Cinnamomum camphora (L.) J. Presl belonging to the family Lauraceae occurs naturally, and native to India, China, Japan, Mongolia, Taiwan, and Bhutan, but has been naturalised in other parts of the World (1)(2)(3)(4)(5)(6)(7)(8). Cinnamomum belongs to the family Lauraceae with about 200-350 species found throughout South East Asia (9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…India accounts for about 40 species of the genus Cinnamomum distributed in Western Ghats, Eastern Himalayas and Andaman Nicobar Islands. Among the total 18 species recorded from south India, 16 are endemic to Western Ghats region (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Now, a new species of the genus Cinnamomum has been identified from Kollam and Thiruvananthapuram districts of Kerala, India (4,(6)(7)(8)(9)(10)(11)14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation